2002
DOI: 10.4049/jimmunol.169.11.6170
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Gene Induction After FcεRI Ligation of Atopic Monocytes Identified by Suppression Subtractive Hybridization

Abstract: The high-affinity receptor for IgE, FcεRI, on APCs plays an important role in the initiation and chronicity of inflammatory atopic diseases. To understand the molecular regulation of FcεRI-mediated processes, differentially expressed genes are of great interest to be identified. Suppression subtractive cDNA hybridization has been used to identify genes induced after FcεRI stimulation on atopic monocytes. Overexpression of the identified genes was determined by semiquantitative RT-PCR analysis of transcripts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
(23 reference statements)
0
15
0
Order By: Relevance
“…FceRI stimulation and efficient allergen uptake and presentation to T cells are central mechanisms of allergic diseases. Stimulation of FceRI on monocytes promotes NF-jB signalling (28), prevents Fas/Fas-L-mediated apoptosis (29), induces the production of IL-10 (23), upregulates the expression of indoleamine dioxygenase (IDO) and favours the release of proinflammatory mediators such as IL-6, monocytes chemoattractant protein (MCP)-1 or macrophage inflammatory protein (MIP)-1b (30). In addition, FceRI stimulation and consequent IL-10 secretion profoundly promote the differentiation of MФ, while preventing the differentiation of CD1a pos DCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…FceRI stimulation and efficient allergen uptake and presentation to T cells are central mechanisms of allergic diseases. Stimulation of FceRI on monocytes promotes NF-jB signalling (28), prevents Fas/Fas-L-mediated apoptosis (29), induces the production of IL-10 (23), upregulates the expression of indoleamine dioxygenase (IDO) and favours the release of proinflammatory mediators such as IL-6, monocytes chemoattractant protein (MCP)-1 or macrophage inflammatory protein (MIP)-1b (30). In addition, FceRI stimulation and consequent IL-10 secretion profoundly promote the differentiation of MФ, while preventing the differentiation of CD1a pos DCs (23).…”
Section: Discussionmentioning
confidence: 99%
“…Then single-stranded complementary DNA (cDNA) was synthesized from 1 µg of RNA using 0.5 nmol of each random primer and subjected to PCR. Subsequently, the synthesized cDNA was amplified using specific sets of primers for mouse MCP-1 (forward, ATGCAGGTCCCTGTCATG; reverse, GCTTGAGGTGGTTGTGGA) (21), mouse GAPDH (forward, TGAAGGTCGGTGTGAACGGATTTGGC; reverse, CATGTAGGCCATGAGGTCCACC AC) (21), human MCP-1 (forward, GACCACCTGGACAAGCAAAC; reverse, CTCAAAACATCCCAGGGGTA) (22), human RhoA (forward, CTGGTGATTGTTGGTGATGG; reverse, GCGAT-CATAATCTTCCTGCC) (23), and human β-actin (forward, GAGCGGGAAATCGTGCGTGACATT; reverse, GATG-GAGTTGAAGGTAGTTTCGTG) (22). The PCR procedure used has been described previously (21)(22)(23).…”
Section: Methodsmentioning
confidence: 99%
“…DC generated from monocyte precursors in a reducing milieu resemble IDEC in their immunophenotype and produce IL-1α, IL-1β, MCP-1, MCP-3, released on activation, normal T-cell expressed and secreted (RANTES), TNF-α, and MIP-1α on FcεRI crosslinking [34]. Using subtractive hybridization, it could be shown that monocytes from atopic donors can produce transcripts for some of the above-mentioned factors as well as MIP-1β, IL-6, IL-1R antagonist, and kynurenine 3-monooxygenase [40]. LClike DC produce IL-16 upon FcεRI ligation, which serves as a chemoattractant for other DC [41•].…”
Section: Fcεri On Antigen-presenting Cells Is Involved In Antigen Focmentioning
confidence: 98%